Implementasi Kebijakan Pariwisata Desa: Tantangan dan Peluang di Desa Ensaid Panjang - -, Nikodimus (Universitas Kapuas Sintang, 2024)
This research aims to examine the implementation of village tourism policies in Ensaid PanjangVillage, Sintang Regency, West Kalimantan, with a focus on the challenges and opportunities faced. Aqualitative approach was used in this research, which involved literature study, in-depth interviews withstakeholders, and participant observation in the field. The research results identified several mainchallenges, including limited infrastructure such as road access and basic facilities, limited skilled humanresources in the tourism sector, and inadequate funding for village tourism development. The proposeddevelopment strategy includes improving basic infrastructure, providing tourism training and educationfor local communities, developing tourism packages that highlight cultural and natural riches, increasingpromotion through digital media, and increasing community participation in tourism management. It ishoped that the implementation of these strategies can encourage sustainable tourism development in EnsaidPanjang Village, providing equitable economic, social and environmental benefits for the entirecommunity. The research conclusion emphasizes the importance of collaboration between government, localcommunities, academics and tourism industry players to achieve inclusive and sustainable tourismdevelopment goals